2017
DOI: 10.1007/s10984-017-9246-9
|View full text |Cite
|
Sign up to set email alerts
|

Is problem-based learning associated with students’ motivation? A quantitative and qualitative study

Abstract: In this study, a mixed-method design was employed to investigate the association between a student-centred, problem-based learning (PBL) method and law students' motivation. Self-determination theory (SDT) states that autonomous motivation, which is associated with higher academic performance, can be reached when there is fulfillment of three psychological needs: autonomy, competence and relatedness. PBL aims to trigger autonomous motivation. In Study 1, 85 PBL law students (37% male; Mean age = 21.99 years) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
0
27
0
1
Order By: Relevance
“…Results show that students in the active learning condition, compared to the passive learning condition, have significantly higher interest, enjoyment, and conceptual learning. Recently, quasi-experimental studies have found that service learning courses enhance perceived autonomy support, autonomous motivation, and internalisation (Levesque-Bristol & Stanek, 2009), and that problembased learning increases relatedness (Wijnen et al, 2017).…”
Section: Collaborative Learningmentioning
confidence: 99%
“…Results show that students in the active learning condition, compared to the passive learning condition, have significantly higher interest, enjoyment, and conceptual learning. Recently, quasi-experimental studies have found that service learning courses enhance perceived autonomy support, autonomous motivation, and internalisation (Levesque-Bristol & Stanek, 2009), and that problembased learning increases relatedness (Wijnen et al, 2017).…”
Section: Collaborative Learningmentioning
confidence: 99%
“…On the other hand, there have been LE studies of various psychosocial measures that relate to both wellbeing and motivation (Salmi and Thuneberg 2018) and that have combined psychosocial outcomes with physical contextual factors (Liu et al 2012). These include both quantitative and qualitative studies that utilise SDT as an organising framework (Alfassi 2004;Wijnen et al 2018). However, to the best of the researcher's knowledge, no work to date has explored the shaping of natural environments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Bringing together the theoretical and methodological assertions presented in the previous sections, we propose a general frame for designing active online/blended courses, with four stages (adapted from Quinn et al, 2014;Windschitl et al, 2018Windschitl et al, , 2020. They are different facets of effective practice that can be connected for promoting successful teaching actions (Figure 1 Taking the case of science teaching and learning course (pre-service teacher education, fourth semester), we create the opportunity for knowledge to be constructed by the students, using a problem-based learning approach, which was previously associated with greater relatedness, autonomy, and control, but also with an increase of intrinsic motivation (Wijnen et al, 2018), reduced students stress (Moffat et al, 2004), retention of information, and critical thinking skills (Schwartz et al, 2001). The activity is online managed using a platform that features the option of breakout rooms/channels (e.g., Microsoft Teams, Zoom, and Google Meet).…”
Section: Guidelines For Course Design In Online Settingsmentioning
confidence: 99%